The Effect of Taxation on Financial Services on Economic Growth in Iran - amir jabbari; narges moradkhani; shiva habibzadeh (پژوهشهای اقتصادی, 2023)
Findings The results show that the rate of social welfare resulting from the imposition of a tax on financial services at the tax rate of 4% (optimal rate) is the highest and the tax rate is 9% for insurance services at the optimal rate. Discussion and Conclusion One of the important results of this research is the changes in government tax revenue that stem from taxes on financial and insurance services in Iran. It is observed that tax revenues have increased due to both tax regimes and the tax revenues from the financial services are higher than tax revenues from insurance services. This shows that financial services in Iran economic space have more tax capacity than insurance services. Looking at the Iranian economy in recent years, it is considered that the economic variables do not depict acceptable conditions. Despite the inflation rate reaching over 47%, it is expected that the Iranian economy will experience a decrease of more than 7% in GDP while the unemployment rate will also increase. Examination of livelihood variables also shows a decline in the consumption level of Iranian households for basic goods. Additionally, during these years, capital accumulation has significantly decreased, and for some production sectors, there is negative capital accumulation. The mentioned situation of the Iranian economy variables shows that Iran is deviated from its long-term growth path and production capacity in Iran's economy is severely degraded. As a result, Iran's economy will be poorer than before and this poverty will reduce consumption.Considering these economic variables, indicators, and research results, such taxes should be applied with great caution, as based on the current economic realities and welfare of society, it can be said that any new tax base until the relative stabilization of the economy and inflation control would result in reducing the consumption of low-income consumers in favor of the government, leading to more unjustified inflation. Keywords: Financial Services, Economic Growth, Social Welfare, Taxes, Computable General Equilibrium Model JEL Classification: C68, F43, G21, H21